MXene-edge graphene oxide heterojunction / PBO fiber multifunctional heat-conducting composite film and preparation method thereof
By designing a multifunctional thermal composite film of MXene-edge graphene oxide heterojunction and polyptyrene benzobisoxazole fiber, the existing thermal composite materials are solved, and efficient thermal management and electromagnetic shielding performance are achieved.
Patent Information
- Application Number
- CN202510034972.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-09
AI Technical Summary
While improving thermal conductivity, existing thermal composite materials are difficult to meet the requirements of mechanical properties, electrical conductivity, electromagnetic shielding and flame retardant properties at the same time, especially in flexible electronic equipment applications, there are problems of thermal aggregation and electromagnetic interference.
By designing a multifunctional thermal composite film of MXene-edge graphene oxide heterojunction and polyp-phenyl benzobisoxazole fiber, the sol-gel-film conversion technology is used, combining covalent bond bridging and π-π interaction, the interface thermal resistance between the fillers is reduced, and the electromagnetic shielding performance is enhanced through the layered structure.
The thermal conductivity coefficient has been significantly improved, the maximum in-plane thermal conductivity reaches 22.2±0.4W m-1K-1, and the electromagnetic shielding performance reaches 59.8dB. At the same time, the mechanical and electrical conductivity are improved, and it is suitable for thermal management and electromagnetic shielding of flexible electronic equipment.
Smart Images

Figure CN119823426A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and in particular to a MXene-edge graphene oxide heterojunction / poly(p-phenylene benzobisoxazole) fiber multifunctional thermal conductive composite film and a preparation method thereof. Background Art
[0002] With the rapid development of high-tech technologies such as artificial intelligence, 5G communications, the Internet of Things, and big data, equipment is constantly moving towards miniaturization, integration, and intelligence. However, the increase in equipment power density leads to a rapid accumulation of heat generated by equipment and devices during operation, which inevitably leads to heat accumulation problems, affecting the operating performance, life, and reliability of the equipment and its components; and the resulting electromagnetic wave radiation will also interfere with the normal operation of surrounding equipment and components. Therefore, it is imperative to design and develop multifunctional composite materials that integrate thermal conductivity and electromagnetic shielding.
[0003] Polymers filled with heterostructured thermally conductive fillers tend to have better thermal conductivity, which is mainly attributed to the fact that the construction of heterostructures can increase the contact between fillers and reduce interfacial thermal resistance and agglomeration. In addition, by designing heterostructures, the advantages of each material can be maximized, reflecting the functional synergy effect of "1+1 is greater than 2". In previous studies, the article "Multifunctional Thermally Conductive Composite Films Based on FungalTree-like Heterostructured Silver Nanowires@Boron Nitride NanosheetsandAramid Nanofibers" [1] The "fungal tree"-like heterostructured silver nanowire@boron nitride nanosheet (AgNWs@BNNS) thermal conductive filler was prepared by in-situ growth method, and the thermal conductive AgNWs@BNNS / ANF composite film was obtained by "suction filtration self-assembly and hot pressing". When the mass fraction of AgNWs@BNNS is 50wt%, the AgNWs@BNNS / ANF composite film has a thermal conductivity of 9.44Wm -1 K -1 The article "Thermal conductivity enhancement of CNT / MoS2 / graphene-epoxy nanocomposites based on structural synergistic effects and interpenetrating network" [2]Carbon nanotube (CNT) / molybdenum disulfide (MoS2) / graphene heterostructure thermal conductive filler was synthesized by hydrothermal method. During the hydrothermal reaction, MoS2 and graphene grew and wrapped on CNT, thus ensuring better interface contact. CNT is both a structural skeleton and a heat transfer channel, which can effectively collect heat from large surface area MoS2 and graphene nanosheets. MoS2 with good wettability further reduces the interfacial thermal resistance between the heterostructure filler and the polymer matrix. The thermal conductivity can reach 4.6Wm -1 K -1 .
[0004] In the study of PBO as the matrix, the article "Mechanically strong and folding-endurance Ti3C2T x MXene / PBO nanofiber films for efficient electromagnetic interference shielding and thermal management” [3] In the f-Ti3C2T x As a composite material, a composite film is obtained by the preparation method of "sol-gel-film" conversion. x When the content reaches 90%, the in-plane thermal conductivity is 5.82W m -1 K -1 Therefore, further improving the thermal conductivity of PBO films has become the focus of current research.
[0005] References:
[0006] [1]Han Y, Ruan K, Gu J.Multifunctional Thermally Conductive CompositeFilms Based on Fungal Tree-like Heterostructured Silver Nanowires@BoronNitride Nanosheets and Aramid Nanofibers[J]. Angewandte Chemie International Edition, 2022, 62: 1-7.
[0007] [2] Ji C, Yan C, Wang Y, et al. Thermal conductivity enhancement of CNT / MoS2 / graphene-epoxy nanocomposites based on structural synergistic effects and interpenetrating network[J]. Composites Part B: Engineering, 2018, 163: 363-370.
[0008] [3] Wang L, Ma Z, Zhang Y, et al. Mechanically strong and folding-endurance Ti3C2Tx MXene / PBO nanofiber films for efficient electromagnetic interference shielding and thermal management[J]. Carbon Energy, 2022, 4: 200–210. Summary of the Invention
[0009] Based on the problems existing in the above-mentioned prior art, the present invention provides a MXene-edge graphene oxide heterojunction / poly(p-phenylene benzobisoxazole) fiber multifunctional thermal conductive composite film (MEOG / PNFs) and a preparation method thereof. The present invention purposefully designs a lateral heterostructure filler, assembles edge graphene oxide (EOG) with MXene (MEOG), and uses covalent bond bridging between fillers to effectively reduce the interfacial thermal resistance ITR between fillers, reduce phonon scattering between fillers, and give full play to the intrinsic thermal conductivity of fillers. On the other hand, in view of the limitations of traditional graphene oxide (GO), the present invention maximizes the lattice integrity within the graphene surface by preparing EOG, which is conducive to the transmission of phonons. In addition, in order to better meet the application requirements of flexible electronic devices, the present invention adopts sol-gel-membrane conversion technology to introduce MEOG heterojunction fillers into poly(p-phenylene benzobisoxazole) nanofibers to prepare a multifunctional composite film, which is combined with PNFs through hydrogen bonds and π-π interactions on the surface of the filler to achieve the purpose of reducing the interfacial thermal resistance between the filler and the matrix, thereby further obtaining a better thermal conductivity. The present invention uses density functional theory (DFT) to explore the interface between heterojunction structure fillers and the bonding force between them and the matrix interface, and explores the formation of its heat conduction path. Heat transfer performance and molecular dynamics (MD) simulations verify the covalent bonds of MEOG and its advantages in solving ITR. At the same time, in order to have a wider range of application scenarios, the system is designed for the mechanical properties, electrical conductivity, electromagnetic shielding properties and flame retardant properties of the composite material. This study provides a new idea for designing effective heterojunction structure multifunctional thermal conductive materials to reduce ITR in thermal conductive composite materials.
[0010] In order to achieve the purpose, the present invention adopts the following technical scheme:
[0011] The present invention provides a method for preparing a MXene-edge graphene oxide heterojunction / PBO fiber multifunctional thermal conductive composite film: firstly, MXene and edge graphene oxide EOG are subjected to nucleophilic substitution and dehydration reaction to obtain a MXene-edge graphene oxide heterojunction filler, which is recorded as a MEOG filler; then the MEOG filler is added to a dispersion of PBO fibers to obtain an acid gel, and then a hydrogel is obtained by replacement with deionized water; finally, the obtained hydrogel is hot-pressed to obtain the multifunctional thermal conductive composite film. Specifically, the method comprises the following steps:
[0012] Step 1: Preparation of MEOG filler
[0013] Disperse MXene in deionized water at a concentration of 1 to 2 mg / mL to obtain a MXene dispersion; disperse EOG in deionized water at a concentration of 1 to 2 mg / mL to obtain an EGO dispersion; according to a mass ratio of MXene to EOG of 10% to 50%: 90% to 50%, ultrasonically mix the MXene dispersion and the EOG dispersion evenly, react at room temperature for 10 to 13 hours to allow MXene and EOG to fully react, then obtain a solid by vacuum-assisted filtration and centrifugation, and vacuum dry to obtain a MEOG filler.
[0014] Step 2: Preparation of PNFs
[0015] Mix methanesulfonic acid (MSA) and trifluoroacetic acid (TFA) in a mass ratio of 1:0.9-1.1 to obtain a mixed acid;
[0016] According to the mass ratio of PBO fiber to mixed acid of 1:95-105, PBO fiber is added to mixed acid, stirred at room temperature for 3-4 days, and a first PNFs dispersion is obtained; the mixed acid is added to the first PNFs dispersion for dilution, and a second PNFs dispersion with a concentration of 0.1-0.15wt% is obtained. After the micron-sized PBO fiber is uniformly dispersed in the mixed acid, nanofibers are formed, which are named PNFs.
[0017] Step 3: Preparation of MEOG / PNFs multifunctional thermal conductive composite film
[0018] The MEOG filler obtained in step 1 is added to the second PNFs dispersion and ultrasonicated for 2 to 2.5 hours to form a viscous sol, and then the first PNFs dispersion is added and stirred evenly, and then Na2SO4 is added and stirred for 3 to 3.5 hours to obtain an acid sol; the acid sol is poured into a mold and solidified at 0 to 6°C for 12 to 16 hours to form an acid gel;
[0019] Immersing the acid gel in deionized water to exchange the solvent for 1 to 3 hours, then changing the water to exchange the solvent again, repeating the exchange 10 to 12 times to obtain a hydrogel;
[0020] The hydrogel is subjected to heat pressing to obtain a MEOG / PNFs multifunctional thermally conductive composite film.
[0021] Furthermore, in step 1, the vacuum drying is carried out at a temperature of 55 to 65° C. and for a time of 11 to 13 hours.
[0022] Furthermore, in step 3, the volume ratio of the second PNFs dispersion to the first PNFs dispersion is 1.5 to 2.5:1.
[0023] Furthermore, in step 3, the ratio of the amount of Na2SO4 added to the total volume of the second PNFs dispersion and the first PNFs dispersion is 1 to 3 g / 60 mL.
[0024] Furthermore, the mass percentage of MEOG filler in the MEOG / PNFs multifunctional thermally conductive composite film is 10-50%.
[0025] The beneficial effects of the present invention are embodied in:
[0026] The present invention prepares edge carboxyl graphene by an improved Hummers method, giving the material a complete in-plane structure, reducing phonon in-plane scattering, and improving the thermal conductivity of the material; MEOG heterojunction thermal conductive filler is prepared by nucleophilic substitution and dehydration reaction, and a covalent bond is constructed between MXene and EOG to reduce the interface thermal resistance between fillers and fillers; it is further compounded with a PNFs matrix, and an additional thermal conductive bridge is provided through the π-π interaction and hydrogen bond interaction between the filler and the matrix, which is conducive to improving the thermal conductivity of the material. Subsequently, a hydrogel is prepared by a replacement method, and a film with a layered stacking structure is prepared by a hot pressing method. The rich interfaces in the layered structure of the film can enhance the multiple reflections and scattering of electromagnetic waves, thereby enhancing the reabsorption and attenuation of electromagnetic waves, so that it has excellent electromagnetic shielding performance. The good layered structure of MEOG / PNFs is more conducive to the interaction between the filler and the matrix. Hydrogen bonds, π-π interactions and van der Waals forces are the connecting bridges between the one-dimensional PNFs and the two-dimensional MEOG nanosheets, which are also conducive to improving the mechanical properties of the film. When the filler content is 40wt%, the maximum in-plane thermal conductivity of the film is 22.2±0.4W m -1 K -1 , which is 900% higher than the blank PNFs sample. The electromagnetic shielding performance of the film reaches 59.8dB at a thickness of 72μm, the maximum tensile strength reaches 176.3±1.3MPa, and the elongation at break is 36.9±1.0%. It can be widely used in electronic equipment for EMI shielding performance and heat dissipation. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Schematic diagram of the preparation process of MEOG / PNFs multifunctional thermal conductive composite film.
[0028] Figure 2 Comparison of thermal conductivity of MEOG / PNFs composite films made from MEOG heterojunction fillers with different MXene:EOG ratios in Examples 1 to 5 and Comparative Examples 1 to 2.
[0029] Figure 3 The thermal conductivity of MEOG / PNFs composite films with different MEOG filler contents prepared in Examples 6 to 10 and Comparative Examples 3 to 4 is compared.
[0030] Figure 4 Schematic diagram of molecular dynamics simulation data of MEOG and PNFs, where: (a) is the molecular dynamics model diagram of MEOG; (b) is the steady-state temperature distribution diagram; (c) is the interface heat transfer data diagram; (de) is the phonon state density of fillers and PNFs.
[0031] Figure 5 Schematic diagram of the thermal conduction mechanism of MEOG / PNFs composite film.
[0032] Figure 6 The electromagnetic shielding performance of the MEOG / PNFs composite films prepared in Examples 6 to 10 and Comparative Examples 3 to 4, wherein (a) is SE T , (b) is SE A , (c) is SE R .
[0033] Figure 7 Schematic diagram of the electromagnetic shielding mechanism of MEOG / PNFs composite film.
[0034] Figure 8 1 and 2. The stress-strain curves of the MEOG / PNFs composite films prepared in Examples 6 to 10 and Comparative Example 4. DETAILED DESCRIPTION
[0035] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiment.
[0036] In the following examples, the preparation method of the MXene used is as follows: 2g Ti3AlC2 powder is slowly added to a mixed solution containing 2g LiF and 40mL 9mol / L HCl. The mixture is then stirred and reacted at 35°C for 24h. After the reaction is completed, the obtained product is centrifuged and washed with deionized water several times until the pH is ~6. The washed sediment is dispersed in 100mL deionized water and ultrasonicated in an ice bath for 1h. Then centrifuged at 4000rpm for 8min to separate the unetched Ti3AlC2. Finally, the supernatant is freeze-dried to obtain Ti3C2T x MXene nanosheets.
[0037] In the following examples, the preparation method of EOG used is as follows: 3.0 g of graphite is dispersed in 138 mL of 98% concentrated sulfuric acid, and the system temperature is maintained at 0°C. After complete dispersion, 50 mL of deionized water is slowly added dropwise, and the system temperature is kept below 70°C to obtain solution A. 18.0 g of potassium permanganate is dissolved in 200 mL of deionized water to obtain solution B. Solution B is slowly added dropwise to solution A, the temperature is raised to 70°C, the reaction is stirred for 24 hours, centrifuged for washing, and freeze-dried to obtain an EOG sample.
[0038] In the following embodiments, the thermal conductivity was measured using a thermal conductivity meter (Hot Disk TP3500, Kegonas Instrument Trading Shanghai Co., Ltd.), the mechanical properties of the composite materials were measured using a universal material testing machine (Instron 5967, USA), and the electromagnetic interference shielding performance was measured using a vector network analyzer (Anritsu MS46322B, Japan).
[0039] 1. Effect of the mass ratio of MXene to EOG in MEOG filler on the properties of composite films
[0040] Example 1
[0041] In this example, the MEOG / PNFs multifunctional thermally conductive composite film was prepared according to the following steps:
[0042] Step 1: Preparation of MEOG filler
[0043] MXene was dispersed in deionized water at a concentration of 1 mg / mL to obtain a MXene dispersion; EOG was dispersed in deionized water at a concentration of 1 mg / mL to obtain an EGO dispersion; the MXene dispersion and the EOG dispersion were ultrasonically mixed evenly according to a mass ratio of MXene to EOG of 4:6, and reacted at room temperature for 12 hours to allow MXene and EOG to fully react, and then a solid was obtained by vacuum assisted filtration and centrifugation, and vacuum dried at 60°C for 12 hours to obtain MEOG filler.
[0044] Step 2: Preparation of PNFs
[0045] Methanesulfonic acid (MSA) and trifluoroacetic acid (TFA) are mixed uniformly in a mass ratio of 1:1 to obtain a mixed acid;
[0046] According to the mass ratio of PBO fiber to mixed acid being 1:100, PBO fiber was added to the mixed acid and stirred at room temperature for 3 days to obtain a first PNFs dispersion; mixed acid was added to the first PNFs dispersion for dilution to obtain a second PNFs dispersion with a concentration of 0.1wt%.
[0047] Step 3: Preparation of MEOG / PNFs multifunctional thermal conductive composite film
[0048] The MEOG filler obtained in step 1 was added to 40 mL of the second PNFs dispersion and ultrasonicated for 2 h to form a viscous sol, and then 20 mL of the first PNFs dispersion was added and stirred evenly, and then 2 g of Na2SO4 was added and stirred for 3 h to obtain an acid sol; the acid sol was poured into a mold and solidified at 5°C for 12 h to form an acid gel;
[0049] The acid gel was immersed in deionized water to exchange the solvent for 1 h, and then the water was changed to exchange again, and the exchange was repeated 12 times to obtain a hydrogel;
[0050] The hydrogel was hot pressed (60° C., 15 KPa) to obtain a MEOG / PNFs multifunctional thermally conductive composite film with a filler content of 5%.
[0051] Example 2
[0052] In this example, the MEOG / PNFs multifunctional thermally conductive composite film was prepared according to the following steps:
[0053] Step 1: Preparation of MEOG filler
[0054] MXene was dispersed in deionized water at a concentration of 1 mg / mL to obtain a MXene dispersion; EOG was dispersed in deionized water at a concentration of 1 mg / mL to obtain an EGO dispersion; the MXene dispersion and the EOG dispersion were ultrasonically mixed evenly according to a mass ratio of MXene to EOG of 1:9, and then reacted at room temperature for 12 hours to allow MXene and EOG to fully react, and then a solid was obtained by vacuum assisted filtration and centrifugation, and vacuum dried at 60°C for 12 hours to obtain MEOG filler.
[0055] Step 2: Preparation of PNFs
[0056] Same as Example 1.
[0057] Step 3: Preparation of MEOG / PNFs multifunctional thermal conductive composite film
[0058] Same as Example 1.
[0059] Example 3
[0060] In this example, the MEOG / PNFs multifunctional thermally conductive composite film was prepared according to the following steps:
[0061] Step 1: Preparation of MEOG filler
[0062] MXene was dispersed in deionized water at a concentration of 1 mg / mL to obtain a MXene dispersion; EOG was dispersed in deionized water at a concentration of 1 mg / mL to obtain an EGO dispersion; the MXene dispersion and the EOG dispersion were ultrasonically mixed evenly according to a mass ratio of MXene to EOG of 2:8, and then reacted at room temperature for 12 hours to allow MXene and EOG to fully react, and then a solid was obtained by vacuum assisted filtration and centrifugation, and vacuum dried at 60°C for 12 hours to obtain MEOG filler.
[0063] Step 2: Preparation of PNFs
[0064] Same as Example 1.
[0065] Step 3: Preparation of MEOG / PNFs multifunctional thermal conductive composite film
[0066] Same as Example 1.
[0067] Example 4
[0068] In this example, the MEOG / PNFs multifunctional thermally conductive composite film was prepared according to the following steps:
[0069] Step 1: Preparation of MEOG filler
[0070] MXene was dispersed in deionized water at a concentration of 1 mg / mL to obtain a MXene dispersion; EOG was dispersed in deionized water at a concentration of 1 mg / mL to obtain an EGO dispersion; the MXene dispersion and the EOG dispersion were ultrasonically mixed evenly according to a mass ratio of MXene to EOG of 3:7, and then reacted at room temperature for 12 hours to allow MXene and EOG to fully react, and then a solid was obtained by vacuum assisted filtration and centrifugation, and vacuum dried at 60°C for 12 hours to obtain MEOG filler.
[0071] Step 2: Preparation of PNFs
[0072] Same as Example 1.
[0073] Step 3: Preparation of MEOG / PNFs multifunctional thermal conductive composite film
[0074] Same as Example 1.
[0075] Example 5
[0076] In this example, the MEOG / PNFs multifunctional thermally conductive composite film was prepared according to the following steps:
[0077] Step 1: Preparation of MEOG filler
[0078] MXene was dispersed in deionized water at a concentration of 1 mg / mL to obtain a MXene dispersion; EOG was dispersed in deionized water at a concentration of 1 mg / mL to obtain an EGO dispersion; the MXene dispersion and the EOG dispersion were ultrasonically mixed evenly according to a mass ratio of MXene to EOG of 5:5, and then reacted at room temperature for 12 hours to allow MXene and EOG to fully react, and then a solid was obtained by vacuum assisted filtration and centrifugation, and vacuum dried at 60°C for 12 hours to obtain MEOG filler.
[0079] Step 2: Preparation of PNFs
[0080] Same as Example 1.
[0081] Step 3: Preparation of MEOG / PNFs multifunctional thermal conductive composite film
[0082] Same as Example 1.
[0083] Comparative Example 1
[0084] In this comparative example, an EOG / PNFs composite film with a filler content of 5% was prepared according to the same method as in Example 1, except that the MEOG filler in step 3 of Example 1 was replaced with an equal amount of EOG filler (i.e., the mass ratio of MXene to EOG was 0:10).
[0085] Comparative Example 2
[0086] In this comparative example, a MXene / PNFs composite film with a filler content of 5% was prepared according to the same method as in Example 1, except that the MEOG filler in step 3 of Example 1 was replaced with an equal amount of MXene filler (i.e., the mass ratio of MXene to EOG was 10:0).
[0087] Figure 2 The thermal conductivity of the MEOG / PNFs composite film prepared by using MEOG heterojunction fillers with different MXene:EOG ratios at the same content (5%) in Examples 1 to 5 and Comparative Examples 1 to 2 shows that when the ratio of MXene to EOG in MEOG is 2:8, the material has the highest thermal conductivity of 7.6 W m -1 K -1 .
[0088] 2. The influence of filler content ratio on the performance of composite films
[0089] Example 6
[0090] In this example, the MEOG / PNFs thermally conductive multifunctional film was prepared according to the following steps:
[0091] Step 1: Preparation of MEOG filler
[0092] MXene was dispersed in deionized water at a concentration of 1 mg / mL to obtain a MXene dispersion; EOG was dispersed in deionized water at a concentration of 1 mg / mL to obtain an EGO dispersion; the MXene dispersion and the EOG dispersion were ultrasonically mixed evenly according to a mass ratio of MXene to EOG of 2:8, and then reacted at room temperature for 12 hours to allow MXene and EOG to fully react, and then a solid was obtained by vacuum assisted filtration and centrifugation, and vacuum dried at 60°C for 12 hours to obtain MEOG filler.
[0093] Step 2: Preparation of PNFs
[0094] Same as Example 1.
[0095] Step 3: Preparation of MEOG / PNFs multifunctional thermal conductive composite film
[0096] 1.623 g of the MEOG filler obtained in step 1 was added to 40 mL of the second PNFs dispersion and ultrasonicated for 2 h to form a viscous sol, and then 20 mL of the first PNFs dispersion was added and stirred evenly, and then 2 g of Na2SO4 was added and stirred for 3 h to obtain an acid sol; the acid sol was poured into a mold and solidified at 5°C for 12 h to form an acid gel;
[0097] The acid gel was immersed in deionized water to exchange the solvent for 1 hour, and then the water was changed and exchanged again, and the exchange was repeated 12 times to obtain a hydrogel; the hydrogel was hot pressed (60°C, 15Kpa) to obtain a MEOG / PNFs multifunctional thermal conductive composite film with a filler content of 40%.
[0098] Example 7
[0099] In this example, the MEOG / PNFs thermally conductive multifunctional film was prepared according to the following steps:
[0100] Step 1: Preparation of MEOG filler
[0101] Same as Example 6.
[0102] Step 2: Preparation of PNFs
[0103] Same as Example 6.
[0104] Step 3: Preparation of MEOG / PNFs multifunctional thermal conductive composite film
[0105] 0.26 g of the MEOG filler obtained in step 1 was added to 40 mL of the second PNFs dispersion and ultrasonicated for 2 h to form a viscous sol, and then 20 mL of the first PNFs dispersion was added and stirred evenly, and then 2 g of Na2SO4 was added and stirred for 3 h to obtain an acid sol; the acid sol was poured into a mold and solidified at 5°C for 12 h to form an acid gel;
[0106] The acid gel was immersed in deionized water to exchange the solvent for 1 hour, and then the water was changed and exchanged again, and the exchange was repeated 12 times to obtain a hydrogel; the hydrogel was hot pressed (60°C, 15Kpa) to obtain a MEOG / PNFs multifunctional thermal conductive composite film with a filler content of 10%.
[0107] Example 8
[0108] In this example, the MEOG / PNFs thermally conductive multifunctional film was prepared according to the following steps:
[0109] Step 1: Preparation of MEOG filler
[0110] Same as Example 6.
[0111] Step 2: Preparation of PNFs
[0112] Same as Example 6.
[0113] Step 3: Preparation of MEOG / PNFs multifunctional thermal conductive composite film
[0114] 0.60 g of the MEOG filler obtained in step 1 was added to 40 mL of the second PNFs dispersion and ultrasonicated for 2 h to form a viscous sol, and then 20 mL of the first PNFs dispersion was added and stirred evenly, and then 2 g of Na2SO4 was added and stirred for 3 h to obtain an acid sol; the acid sol was poured into a mold and solidified at 5°C for 12 h to form an acid gel;
[0115] The acid gel was immersed in deionized water to exchange the solvent for 1 hour, and then the water was changed and exchanged again, and the exchange was repeated 12 times to obtain a hydrogel; the hydrogel was hot pressed (60°C, 15Kpa) to obtain a MEOG / PNFs multifunctional thermal conductive composite film with a filler content of 20%.
[0116] Example 9
[0117] In this example, the MEOG / PNFs thermally conductive multifunctional film was prepared according to the following steps:
[0118] Step 1: Preparation of MEOG filler
[0119] Same as Example 6.
[0120] Step 2: Preparation of PNFs
[0121] Same as Example 6.
[0122] Step 3: Preparation of MEOG / PNFs multifunctional thermal conductive composite film
[0123] 1.03 g of the MEOG filler obtained in step 1 was added to 40 mL of the second PNFs dispersion and ultrasonicated for 2 h to form a viscous sol, and then 20 mL of the first PNFs dispersion was added and stirred evenly, and then 2 g of Na2SO4 was added and stirred for 3 h to obtain an acid sol; the acid sol was poured into a mold and solidified at 5°C for 12 h to form an acid gel;
[0124] The acid gel was immersed in deionized water to exchange the solvent for 1 hour, and then the water was changed and exchanged again, and the exchange was repeated 12 times to obtain a hydrogel; the hydrogel was hot pressed (60°C, 15Kpa) to obtain a MEOG / PNFs multifunctional thermal conductive composite film with a filler content of 30%.
[0125] Example 10
[0126] In this example, the MEOG / PNFs thermally conductive multifunctional film was prepared according to the following steps:
[0127] Step 1: Preparation of MEOG filler
[0128] Same as Example 6.
[0129] Step 2: Preparation of PNFs
[0130] Same as Example 6.
[0131] Step 3: Preparation of MEOG / PNFs multifunctional thermal conductive composite film
[0132] 2.41 g of the MEOG filler obtained in step 1 was added to 40 mL of the second PNFs dispersion and ultrasonicated for 2 h to form a viscous sol, and then 20 mL of the first PNFs dispersion was added and stirred evenly, and then 2 g of Na2SO4 was added and stirred for 3 h to obtain an acid sol; the acid sol was poured into a mold and solidified at 5°C for 12 h to form an acid gel;
[0133] The acid gel was immersed in deionized water to exchange the solvent for 1 hour, and then the water was changed and exchanged again, and the exchange was repeated 12 times to obtain a hydrogel; the hydrogel was hot-pressed (60°C, 15Kpa) to obtain a MEOG / PNFs multifunctional thermal conductive composite film with a filler content of 50%.
[0134] Comparative Example 3
[0135] In this comparative example, an EOG / PNFs composite film with a filler content of 40% was prepared according to the same method as in Example 6, except that the MEOG filler in step 3 of Example 6 was replaced with an equal amount of EOG filler.
[0136] Comparative Example 4
[0137] In this comparative example, a MEOG / PNFs composite film with a filler content of 0% was prepared according to the same method as in Example 6, except that the amount of MEOG filler added in step 3 of Example 6 was 0.
[0138] Figure 3 The thermal conductivity of the composite materials obtained in Examples 6 to 10 of the present invention and Comparative Examples 3 to 4 is compared. It can be seen from the figure that when the content of MEOG is 40wt%, the thermal conductivity of the obtained material is increased by 900% to 22.2W m -1 K -1 By comparing with the single filler EOG / PNFs film, it is shown that the formation of MEOG heterojunction can introduce multiple interactions, which is beneficial to the improvement of thermal conductivity.
[0139] Figure 4 Schematic diagram of molecular dynamics simulation data of MEOG and PNFs. The M-EOG used for comparison is a blend of MXene and EOG in a mass ratio of 2:8, where: (a) is the molecular dynamics model of MEOG; (b) is the steady-state temperature distribution diagram; (c) is the interface heat transfer data diagram; (de) is the phonon state density of the filler and PNFs. The low phonon transmission resistance reflects the highest interfacial thermal conductivity and energy transfer capacity between the EOG and MXene layers. Phonon state density (pDOS) matching is used here to determine the phonon energy transfer efficiency at the interface of MEOG, M-EOG and PNFs. Compared with M-EOG, MEOG has the highest phonon state density peak and also shows the highest spectral overlap ratio (ORIL) with PNFs, verifying the positive effect of multiple non-covalent interactions on reducing ITRf-m. In the in-depth study of the thermal conductivity mechanism of MEOG heterojunction, in order to verify the role of covalent bonds in MEOG in bridging the phonon transmission in the filler, the MEOG and M-EOG models were established to analyze the heat transfer. Figure 4 As shown in (ac), due to the strong covalent interaction between the materials, a more efficient horizontal heat transfer interface structure is formed between the MEOG interface by comparing with the M-EOG model without interaction. When the heat flux in the system is in a steady state, compared with M-EOG, the temperature gradient between adjacent EOG and MXene layers in MEOG is the smallest (ΔT = 35.9K), as shown in Figure 4(b) As shown. Because the strong interaction of covalent bonds strengthens the bonding between different interfaces, it effectively promotes phonon transmission. Compared with the forces between materials in the control sample, covalent interactions make the materials have stronger bonding forces, which is also reflected in the DFT binding energy calculation. The role of covalent bonds is more directly reflected in the interlayer heat transfer of MEOG. The interfacial thermal conductivity (ITC) of MEOG is 3.23GWm -2 K -1 , far exceeding M-EOG.
[0140] Figure 5 Schematic diagram of the thermal conductivity mechanism of MEOG / PNFs composite film, in which the heat flow is transmitted along the distribution direction of the filler. Inside the filler, the tightly bound covalent bonds (Ti-OC) and π-π and hydrogen bonds (Hydrogen bond) interact to promote the further transmission of phonons, which is beneficial to the improvement of the thermal conductivity of the film.
[0141] Figure 6 The electromagnetic shielding performance of the composite films obtained in Examples 6 to 10 of the present invention and Comparative Example 4 is shown in the figure. When the content of MEOG is 40 wt%, SE T 59.8dB, SE A Much higher than SE R , indicating that the absorption of electromagnetic waves is the main shielding mechanism of MEOG / PNFs films.
[0142] Figure 7 The figure is a schematic diagram of the electromagnetic shielding mechanism of MEOG / PNFs composite film, in which electromagnetic wave absorption is the main shielding mechanism of MEOG / PNFs film. When the incident electromagnetic wave reaches the surface of MEOG / PNFs film, due to the impedance mismatch between air and conductive MEOG / PNFs film, part of the electromagnetic wave is directly reflected, and the rest of the electromagnetic wave enters the interior of MEOG / PNFs. The rich interfaces in the layered structure of MEOG / PNFs film can enhance the multiple reflection and scattering of electromagnetic waves, thereby enhancing the reabsorption and attenuation of electromagnetic waves.
[0143] Figure 8 The stress-strain curves of the composite materials obtained in Examples 6 to 10 of the present invention and Comparative Example 4 show that when the content of MEOG is 40 wt %, the maximum tensile strength reaches 176.3 MPa and the elongation at break is 35.9%.
[0144] The above are merely exemplary embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a MXene-edge graphene oxide heterojunction / PBO fiber multifunctional thermal conductive composite film, characterized in that: Firstly, MXene and edge graphene oxide EOG are reacted by nucleophilic substitution and dehydration to obtain MXene-edge graphene oxide heterojunction filler, which is denoted as MEOG filler; then the MEOG filler is added to the dispersion of PBO fiber to obtain acid gel, and then the hydrogel is obtained by deionized water replacement; finally, the obtained hydrogel is hot-pressed to obtain the multifunctional thermal conductive composite film.
2. The preparation method according to claim 1, characterized in that: The steps include: Step 1: Preparation of MEOG filler Dispersing MXene in deionized water at a concentration of 1 to 2 mg / mL to obtain a MXene dispersion; dispersing EOG in deionized water at a concentration of 1 to 2 mg / mL to obtain an EGO dispersion; ultrasonically mixing the MXene dispersion and the EOG dispersion in a mass ratio of 10% to 50%: 90% to 50% of MXene to EOG, reacting at room temperature for 10 to 13 hours, and then obtaining a solid by vacuum assisted filtration and centrifugation, and vacuum drying to obtain a MEOG filler; Step 2: Preparation of PNFs Mix methanesulfonic acid and trifluoroacetic acid in a mass ratio of 1:0.9-1.1 to obtain a mixed acid; According to the mass ratio of PBO fiber to mixed acid of 1:95-105, PBO fiber is added to the mixed acid, and stirred at room temperature for 3-4 days to obtain a first PNFs dispersion; the mixed acid is added to the first PNFs dispersion for dilution to obtain a second PNFs dispersion with a concentration of 0.1-0.15wt%; Step 3: Preparation of MEOG / PNFs multifunctional thermal conductive composite film The MEOG filler obtained in step 1 is added to the second PNFs dispersion and ultrasonicated for 2 to 2.5 hours to form a viscous sol, and then the first PNFs dispersion is added and stirred evenly, and then Na2SO4 is added and stirred for 3 to 3.5 hours to obtain an acid sol; the acid sol is poured into a mold and solidified at 0 to 6°C for 12 to 16 hours to form an acid gel; Immersing the acid gel in deionized water to exchange the solvent for 1 to 3 hours, then changing the water to exchange the solvent again, repeating the exchange 10 to 12 times to obtain a hydrogel; The hydrogel is subjected to heat pressing to obtain a MEOG / PNFs multifunctional thermally conductive composite film.
3. The preparation method according to claim 2, characterized in that: In step 1, the vacuum drying is carried out at a temperature of 55 to 65° C. and for a time of 11 to 13 hours.
4. The preparation method according to claim 2, characterized in that: In step 3, the volume ratio of the second PNFs dispersion to the first PNFs dispersion is 1.5 to 2.5:
1.
5. The preparation method according to claim 2, characterized in that: In step 3, the ratio of the amount of Na2SO4 added to the total volume of the second PNFs dispersion and the first PNFs dispersion is 1 to 3 g / 60 mL.
6. The preparation method according to claim 2, characterized in that: The mass percentage of the MEOG filler in the MEOG / PNFs multifunctional heat-conductive composite film is 10-50%.
7. A MEOG / PNFs multifunctional thermally conductive composite film prepared by the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
MXene and graphene oxide composite aerogel, and preparation method and applications thereof
CN110090603A
Preparation method of titanium carbide MXene functionalized graphene nanocomposite film and application thereof
CN111252768A
Surface modification method of PBO fibers
CN112626845A
Antioxidant MXene-based electromagnetic shielding composite film and preparation method and application thereof
CN118555815A
Light-weight porous mxene-based composite thin film electromagnetic shielding material and preparation method therefor
WO2022242256A1
Cited By
High-thermal-conductivity flame-retardant PBO nano-composite film and preparation method thereof
CN120463991A
PBO-based intelligent flame-retardant early-warning film and preparation method thereof
CN121378817A
A method for preparing a pbo nanofiber film having an in-plane orientation
CN122790260A